Pendidikan Lingkungan Hidup dengan Membentuk Kesadaran Lingkungan dan Tanggung Jawab Sosial di Kalangan Pelajar - Rahayu, Indah; Suwarna, A. Idun; Wahyudi, Eko; Asfahani, Asfahani; Jamin, Fitriah Suryani (Civiliza Publishing, Indonesia., 2024)
Environmental Education (PLH) plays an important role in forming environmental awareness and social responsibility among students. This article aims to explore the effectiveness of PLH. The research method used is a qualitative research method which involves in-depth interviews with teachers and students as well as direct observation in the school environment. The research results show that experience-based learning methods, support from schools and communities, and social interaction are crucial factors in the success of the PLH program. This finding is in line with theories of environmental education and corporate social responsibility which emphasize the importance of real experience, the social environment, and environmental responsibility. In conclusion, the integrated implementation of PLH with support from various parties can be an effective instrument in forming a generation that cares about and is responsible for the environment and society at large.